What Makes for the Most Intense Regrets? Comparing the Effects of Several Theoretical Predictors of Regret Intensity - Towers, Andy; Williams, Matt N.; Hill, Stephen R.; Philipp, Michael C.; Flett, Ross (Frontiers in Psychology, 2016)
Several theories have been proposed to account for variation in the intensity of life regrets. Variables hypothesised to affect the intensity of regret include: whether the regretted decision was an action or an inaction, the degree to which the decision was justified, and the life domain of the regret. No previous study has compared the effects of these key predictors in a single model in order to identify which are most strongly associated with the intensity of life regret. In this study, respondents (N = 500) to a postal survey answered questions concerning the nature of their greatest life regret. A Bayesian regression analysis suggested that regret intensity was greater for—in order of importance—decisions that breached participants’ personal life rules, decisions in social life domains than non-social domains, and decisions that lacked an explicit justification. Although regrets of inaction were more frequent than regrets of action, regrets relating to actions were slightly more intense.